2014
DOI: 10.1155/2014/174581
|View full text |Cite
|
Sign up to set email alerts
|

Beta-Thalassaemia Intermedia: Evaluation of Endocrine and Bone Complications

Abstract: Objective. Data about endocrine and bone disease in nontransfusion-dependent thalassaemia (NTDT) is scanty. The aim of our study was to evaluate these complications in β-TI adult patients. Methods. We studied retrospectively 70 β-TI patients with mean followup of 20 years. Data recorded included age, gender, haemoglobin and ferritin levels, biochemical and endocrine tests, liver iron concentration (LIC) from T2*, transfusion regimen, iron chelation, hydroxyurea, splenectomy, and bone mineralization by dual X-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 35 publications
(36 reference statements)
4
23
0
Order By: Relevance
“…Insulin resistance has been extensively studied among patients with TDT (mainly β‐thalassemia major), and it is known to be related to the severity of iron overload . Meanwhile, studies in NTDT patients (mostly β‐thalassemia intermedia) with iron overload reported variable prevalence of impaired glucose tolerance and DM . However, there are no previous data specific to the role of iron overload in insulin resistance among patients with Hb H disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Insulin resistance has been extensively studied among patients with TDT (mainly β‐thalassemia major), and it is known to be related to the severity of iron overload . Meanwhile, studies in NTDT patients (mostly β‐thalassemia intermedia) with iron overload reported variable prevalence of impaired glucose tolerance and DM . However, there are no previous data specific to the role of iron overload in insulin resistance among patients with Hb H disease.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in adults with NTDT that mainly focused on β‐thalassemia intermedia reported a variable prevalence of impaired glucose tolerance (2.9%‐24%) and DM (1.4%‐4.5%)—both of which were found to be associated with iron overload . However, such studies have been rarely reported in α‐thalassemia hemoglobin H (Hb H) disease, which is the most common form of NTDT worldwide .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actually we believe that is important to define a ''thickening'' of bone, as a bone marrow hyperplasia, according to the pathogenesis of Beta-Thalassemia Major in order to avoid redundant surgery [40] or antibiotic treatment abuse in these critical patients [41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…The factors underlying these differences have not been well studied. The slower rate, lower extent, and hepatic predominance of iron loading in NTDT as compared to TDT are potential factors that could explain the differences in prevalence of endocrinopathies . Factors thought to correlate with endocrinopathies in patients with NTDT include splenectomy, the severity of ineffective erythropoiesis, and lower levels of fetal hemoglobin (HbF) .…”
Section: Clinical Morbidities In Ntdtmentioning
confidence: 99%